DNA Hypermethylation Induced by L-Methionine Leads to Oligodendroglial and Myelin Deficits and Schizophrenia-Like Behaviors in Adolescent Mice - Chen, Xianjun; Huang, Nan-Xin; Cheng, Yong-Jie; Cai, Qi-Yan; Tian, Yan-Ping; Chen, Xing-Shu; Xiao, Lan (Frontiers in Neuroscience, 2021)
Increasing evidence has demonstrated that in addition to dysfunction of neuronal circuitry, oligodendroglial dysfunction and/or disruption of white matter integrity are found in the brains of patients with schizophrenia. DNA methylation, a well-established risk factor for schizophrenia, has been demonstrated to cause neuronal dysfunction; however, whether dysregulation of DNA methylation contributes to oligodendroglial/myelin deficits in the pathogenesis of schizophrenia remains unclear. In the present study, by using L-methionine-treated mice, we confirmed that mice with DNA hypermethylation exhibited an anxious phenotype, impaired sociability and sensorimotor gating deficits. Notably, DNA hypermethylation in oligodendroglial cells led to dysregulation of multiple oligodendroglia-specific transcription factors, which indicated disruption of the transcriptional architecture. Furthermore, DNA hypermethylation caused a reduction of oligodendroglial lineage cells and myelin integrity in the frontal white matter of mice. Taken together, these results indicate that DNA hypermethylation leads to oligodendroglial and/or myelin deficits, which may, at least in part, contribute to schizophrenia-like behaviors in mice. This study provides new insights into the possibility that precise modulation of DNA methylation status in oligodendroglia could be beneficial for the white matter pathology in schizophrenia.